Analisis dan Perancangan Sistem Informasi Penilaian Prestasi Kerja Pegawai pada Universitas Jambi - Hutabarat, Andrella Silvana; Mauladi, Mauladi; Suratno, Tri (JUSS (Jurnal Sains dan Sistem Informasi), 2018)
The appraisal process work achievement officer at University of Jambi is currently based on Government Regulation No. 46 year 2011 about appraisal of work achievements civil servants, which is done once a year. Aspects of appraisal divided into two part, namely Employee Performance Goals (SKP) and Appraisal of Work Behavior. Basis for the appraisal of SKP is based on 4 aspects, namely quantity, quality, time and cost. Appraisal of Work Behaviour based 6 aspects, such as service orientation, integrity, commitment, discipline, cooperation and leadership. To achieve the result of employee performance appraisal required two components that is employee performance target value (60 percents) and work behavior value (40 percents). The final result of this research is design of information systems employee performance appraisal process based on SKP and behavioral appraisal. The method to make the desain using Unified Modelling Language (such as: use case diagram, activity diagram, sequence diagram) and entity relationship diagram. Whereas to rate the user interface design of employee work achievement appraisal information system using System Usability Score (SUS).